Estudo de tempo de resposta do GPIO da BeagleBone Black - Alves, Pedro Henrique Coelho (2017)
The BeagleBone Black is a low-cost professional development platform, compared to other embedded systems platforms, produced by Texas Instruments, capable of starting Linux in less than ten seconds and allowing the programmer to commence working on his project in less than five minutes, using only a single USB cable and a computer as extra hardware. This practicality, as well as its technical specifications, makes the equipment a solid choice for most of the embedded projects that a developer is idealizing. However, the equipment has limitations on frequencies above 8kHz, making its standard use unsuitable for high speed applications. This paper has conducted a study on the response time of the BeagleBone Black, addressing various combinations of development environments and programming languages, in order to ascertain and their respective performances. A secondary objective of this work is also to produce and multiply the content that exists regarding this subject in Portuguese, which is scarce, in order to stimulate its use.